Observational study found that even small variations in light can wake up very preterm infants in a neonatal intensive care unit. (27th February 2018) - Zores, Claire; Dufour, André; Pebayle, Thierry; Dahan, Ilana; Astruc, Dominique; Kuhn, Pierre
Abstract: Aim: This prospective observational study evaluated the behavioural responses of very preterm infants to spontaneous light variations. Methods: We measured spontaneous light variations in the incubators of 27 very preterm infants, with a median gestational age of 28 weeks (range 26–31 weeks), over 10 hours. All of them had been admitted to the neonatal care unit of the Strasbourg University Hospital, France, between April 2008 and July 2009. Two independent raters examined changes in the infants' behavioural states using video recordings. The percentage of awakenings was recorded when there were light variations and during control periods with no changes. Results: We analysed 275 periods following light variations and 275 control periods. The overall percentage of awakenings was greater during periods following a change in light than during control periods (16.3% vs 11%, p = 0.03). The extent of light protection affected the percentage of awakenings. In mild light protection, there were more awakenings following changes in light than in control periods (25.6% vs 6.7%, p = 0.01). This difference was not found in high light protection. Conclusion: Very preterm infants can be woken up by small variations in light, when the light protection in their incubator is insufficient. Abstract :